Best Practice of Corporate Governance pada Lembaga Keuangan Islam (Bank Islam) - Indrawati, Nur Khusniyah (Universitas Brawijaya, Indonesia, 2008)
A number of Islamic Financial Institutions (IFIs) or Islamic Banking has been established is almost every part in the world. On the other hand, conventional banks have also expanded their operation which operates Islamic Windows. This effort is conducted in order to attract depositors from Moslem society, as like as in Malaysia and the other countries. The system gives chance for depositors to choose interest basis or profit-and-loss sharing basis when he or she is going to make a transaction with a bank However, In Indonesia, conventional banks is not permitted to make activity based on Islamic Windows. The Government issued the regulatation UU No. 7 of year 1992 banking system making Islamic Bank legal in the Indonesian banking history and indicates conventional bank are allowed to operate based on the dual banking systems This regulation was amended by regulation UU No. 10 year 1998. Conventional banks with its interst system runs side by side with the Islamic Bank with Profit-and-loss-sharing/PLS basis that is separated from the main bank (conventional bank), such as: Indonesia Muamalat Bank Mandiri Syariah Bank, and Mega Syariah Bank, or establishing Unit Usaha Syariah (UUS). Up until the present the development of Islamic Bank is very rapid in term of number of ventures, offices, fund amassement and chanelling, and types of product. All of those systems primarily Islamic Windows have been internationally accepted. However, it is necessary to have a strength allowing IFIs expands their activities continuously and can be accepted internationally. Moreover, in order to increase IFIs, one of focuses is to create an enabling environment of IFIs to grow. Besides that, it is needed the implementation of Corporate Governance that have been executed for a long time in conventional financial system (conventional bank). Implementation of Corporate Governance is very important for IFIs because depositors in IFIs accepts added risk as an effect of risk sharing for implementation of PLS systems.